2022
DOI: 10.3168/jds.2021-21115
|View full text |Cite
|
Sign up to set email alerts
|

Subacute ruminal acidosis phenotypes in periparturient dairy cows differ in ruminal and salivary bacteria and in the in vitro fermentative activity of their ruminal microbiota

Abstract: Both ruminal microbial structure and functionality might play a role in inter-individual variation in susceptibility for subacute rumen acidosis (SARA) observed in dairy cows. The aims of this study were to determine whether differences between cows with distinct SARA susceptibility were reflected in distinct (1) ruminal microbial communities, (2) salivary bacterial communities, and (3) fermentative capacity of ruminal microbiota assessed in vitro. To test this hypothesis, rumen samples were collected via an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Likewise, using the more commonly applied SARA definition of ruminal pH < 5.8 for > 330 min/d ( Zebeli et al, 2008 ), HIGH cows had SARA for 77% of the experimental period, while LOW cows only in maximum 7% of the experimental days. Varying SARA severities have also been identified in multiparous Holstein cows ( Yang et al, 2022 ), showing that this is a common phenomenon in dairy cattle. However, the SARA intervals of cows with high severity were substantially longer in our study than by Yang et al (2022) , which may be due to the fact that primiparous cows are more prone to SARA than multiparous cows ( Stauder et al, 2020 ) and emphasizes the cows’ vulnerability during the first lactation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Likewise, using the more commonly applied SARA definition of ruminal pH < 5.8 for > 330 min/d ( Zebeli et al, 2008 ), HIGH cows had SARA for 77% of the experimental period, while LOW cows only in maximum 7% of the experimental days. Varying SARA severities have also been identified in multiparous Holstein cows ( Yang et al, 2022 ), showing that this is a common phenomenon in dairy cattle. However, the SARA intervals of cows with high severity were substantially longer in our study than by Yang et al (2022) , which may be due to the fact that primiparous cows are more prone to SARA than multiparous cows ( Stauder et al, 2020 ) and emphasizes the cows’ vulnerability during the first lactation.…”
Section: Discussionmentioning
confidence: 98%
“…Varying SARA severities have also been identified in multiparous Holstein cows ( Yang et al, 2022 ), showing that this is a common phenomenon in dairy cattle. However, the SARA intervals of cows with high severity were substantially longer in our study than by Yang et al (2022) , which may be due to the fact that primiparous cows are more prone to SARA than multiparous cows ( Stauder et al, 2020 ) and emphasizes the cows’ vulnerability during the first lactation. Unexpectedly, cows within each group experienced SARA with almost similar duration throughout the complete experiment, indicating to be rather independent of moderate- or high-grain feeding and feed intake level.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was possible to monitor real-time parameters such as pH, temperature of reticulorumen content (TRR), and cow activity by smaXtec boluses (smaXtec animal care technology ® ) [ 24 , 25 ]. Antennas (smaXtec animal care technology ® ) were used to collect the data.…”
Section: Methodsmentioning
confidence: 99%
“…As such, we aimed to determine if fecal bacterial communities postpartum and prepartum contribute to identifying postpartum SARA susceptibility. The fecal samples of this study were obtained from an experiment with 38 dairy cows, which showed inter-animal variation in SARA susceptibility [23].…”
Section: Introductionmentioning
confidence: 99%